Theoretical study on SH2 reaction of methyl radical with three‐membered ring. Issue 23 (3rd July 2014) - Zhang, Xiang
<x xml:space="preserve">Abstract</x> Bimolecular homolytic substitution (SH2) reactions of the methyl radical with a series of three‐membered ring compounds have been given a systematic theoretical study. These reactions proceed predominantly via the backside displacement. The formation of the new radical product is thermodynamically favorable probably due to the release of the ring strain. Natural bond orbital analysis reveals that SOMO → σ*(C‐X) (X= C, N, O) interaction plays a major role in these SH2 reactions, which shows the methyl radical mainly acts as a nucleophilic radical. In addition, according to the activation strain model analysis, an expected single correlation has not been obtained between the reactant distortion enthalpies and the overall activation enthalpies. However, these reactions can be divided into three groups and each group exhibits a good linear correlation. Marcus theory can thoroughly account for this phenomenon. © 2014 Wiley Periodicals, Inc.